Use of metods of algebraic programming for the formal verification of legal acts - Peschanenko, V.; Poltorackiy, M. (Проблеми програмування, 2018)
This article briefly describes the programmable tool for the analysis of a normative legal document. A mechanism for checking legal requirements is presented. The model of the legal document is proposed in the form of a set of special rules. Verification is provided by means of algebraic programming and methods of symbolic transformation. This approach allows us to analyze the legislative base of structural and logical errors, check the contradictions, completeness and integrity of legal acts. Presently, the mechanism of claster analysis of text, which makes it possible to identify the frequency of occurrence of various vague language constructs. У цій статті коротко описується програмний інструмент для аналізу нормативно-правового документа. Існує механізм перевірки законних вимог. Модель правового документа представлена у вигляді набору спеціальних правил. Верифікація забезпечується за допомогою алгебраїчного програмування та методів символьного програмування. Цей підхід дозволяє проаналізувати законодавчу базу на наявність структурно логічних помилок, перевіряти правові вимоги на протиріччя, повноту та цілісність. В этой статье кратко описывается программный инструмент для анализа нормативного правового документа. Представлен механизм проверки юридических требований. Модель юридического документа представлена в виде набора специальных правил. Верификация обеспечивается с помощью алгебраического программирования и методов символьного преобразования. Такой подход позволяет нам анализировать законодательную базу на наличие структурно-логических ошибок, проверять противоречия, полноту и целостность правовых актов.